Forest biodiversity indicators correlate with perceived forest qualities but not with psychological well-being in urban forests - Korhonen, Aku; Simkin, Jenni; Ojala, Ann; Neuvonen, Marjo; Kauppila, Mathilda; Hamberg, Leena (Elsevier, 2026)
Provision of recreational opportunities and biodiversity are among the most significant values associated with urban forests in Nordic cities. However, catering to both demands with a limited forest area can result in conflicts, which need to be accounted for in urban forest management and land-use planning. In this study, we examined associations between forest biodiversity and on-site experiences of city residents (n = 153) in spruce-dominated urban forests (n = 15) in five Finnish cities. Biodiversity values were assessed from four complementary perspectives including (1) tree species admixture, (2) abundance of dead wood, (3) heterogeneity of ground vegetation, and (4) late-successional ectomycorrhizal fungal richness in the soil. People's experiences were investigated in terms of perceived forest quality and change in felt restoration and energy level before and after the forest visit. We found several correlations between people's perceptions of forest quality and measured biodiversity indicators. The correlations indicated mostly synergistic relationships between forest biodiversity and human preferences. Yet, differences in biodiversity indicators were not reflected in felt restoration or energy level changes. Our results suggest that promoting forest structural features that benefit biodiversity in boreal spruce-dominated forests is mostly in line with urban residents' preferences regarding forest qualities, but that management within forests should enable easy passage through them.
Keywords: boreal forest; mixed forest; dead wood; ground vegetation; ectomycorrhizal fungi; mental well-being